How dark are stalking attitudes? an investigation of individual differences in stalking attitudes and associated behaviour online - Fuller, Millie (2020)
Why are certain individuals more likely to endorse stalking attitudes than others? Is there a relationship between stalking attitudes and an individual’s online behaviour? What characterises the psychological profile of a cyberstalker?